Adaptive pathways of soil microorganisms to stoichiometric imbalances regulate microbial respiration following afforestation in the Loess Plateau, China. (December 2020) - Zhong, Zekun; Li, Wenjie; Lu, Xuqiao; Gu, Yunqi; Wu, Shaojun; Shen, Zhaoyang; Han, Xinhui; Yang, Gaihe; Ren, Chengjie
Abstract: Afforestation results in a wide range of soil resources with carbon (C), nitrogen (N), and phosphorus (P) levels that rarely meet microbial elemental demands. Such stoichiometric imbalances result in the limitation of microbial activity by nutrients, and have consequences for microbial C and nutrient use efficiency and ultimately the fate of soil C. However, how microorganisms cope with stoichiometric imbalances following afforestation and how their responses regulate microbial-driven C emissions remain unclear. We compared sites along a 42 year Robinia pseudoacacia afforestation chronosequence on the Loess Plateau of China, to quantify soil microbial nutrient limitation and explore the mechanisms underlying microbe-mediated C dynamics under conditions of stoichiometric imbalance. Soil available nutrients, potential activities of C-, N-, and P-acquiring enzymes, microbial biomass, microbial community composition and diversity, as well as microbial respiration were measured. Results showed that stoichiometric imbalances increased soil enzymatic activities targeting the mobilization of limiting nutrients at different afforestation stages. Specifically, soil microbial communities were limited by C in farmland, co-limited by N and P at the 10-year site, and became more limited by P as stand age increased. Reductions in stoichiometric imbalance along the afforestation chronosequence corresponded to an increased microbial alpha diversity and fungi-to-bacteria ratio. Stoichiometric imbalances were more strongly associated with changes in soil bacterial beta diversity than fungal beta diversity. Bacterial communities transitioned from being oligotrophic ( Actinobacteria dominant) to copiotrophic ( Proteobacteria dominant) during forest development, and this was significantly related to stoichiometric imbalance. However, no significant correlation was detected between stoichiometric imbalance and the dominant fungal phyla (i.e., Ascomycota, Basidiomycota, and Zygomycota ). The synergistic responses of enzymatic stoichiometry and microbial community properties to stoichiometric imbalance following afforestation led to reduced microbial threshold elemental ratios, which elevated microbial C use efficiency and increased biomass turnover time, further suppressing microbial respiration. Such collaborative-adaptations imply that more C will be diverted into microbial biomass rather than losing, thus could be favorable to soil C storage. Collectively, these findings highlight the importance of stoichiometric imbalances in regulating microbial-driven C emissions and contribute to an improved understanding of how substrate quality changes induced by revegetation influences terrestrial C flows in ecologically fragile areas. Graphical abstract: Image 1 Highlights: Afforestation lowered stoichiometric imbalances and increased soil enzyme activity. Afforesting farmland deregulated microbial C limitation but increased P limitation. Soil bacteria was more sensitive to the C:N:P stoichiometric imbalances than fungi. Forestation reduced microbial threshold elemental ratios, raising C use efficiency. Increased microbial C use efficiency and biomass turnover time reduced respiration.